(untitled) (Research, Society and Development, 2022)
The present work investigates a possible “profile” of violence against women in the municipality of Seropédica/RJ in different time arcs between 2006 and 2019. For its interpretation, we start from theoretical bases that allow us to elaborate a sense of violence against women as one of the manifestations of gender violence. At the same time, we present the legislation and governmental action of the municipality to identify how the theme develops governmentally, while comparing the databases on gender violence in Seropédica. The sense of work allows the public manager to subsidize a profile that comprises a form of violence built by the proximity of the relationship between the victim and the aggressor, in addition to their “invisibility” of the place where it occurs. Likewise, there is a clear context of violence that is not the object of consideration or intervention by the State (in this case, the municipality); while there are institutional mechanisms of mere governmental "appearance".